Development Characteristics of Silurian Strike-Slip Faults and Fractures and Their Effects on Drilling Leakage in Shunbei Area of Tarim Basin - Li, Haiying (Frontiers in Earth Science, 2022)
In recent years, the Ordovician fault-controlled fracture-cavity reservoirs developed in the basement strike-slip fault zone in the Shunbei area of the Tarim Basin has achieved major breakthroughs. However, during the drilling process of the strike-slip fault zone in the Shunbei area, the problem of mud leakage in the frequently interbedded Silurian sandstone and mudstone strata overlying the Ordovician target layer is very significant, and it has seriously affected the normal drilling and wellbore stability. In this study, taking the Silurian of the No. A Strike-slip Fault Zone in the Shunbei area as an example, the development characteristics of strike-slip faults and fractures, the strength of the in-situ stress field, and the influence of these factors on the drilling mud leakage were systematically studied using 3D seismic, logging, drilling, logging, well log, and engineering construction data. The results show that the mud leakage in strata S1t is significantly larger than that in S1k, and the leakage amount in sandy mudstone is the largest; the strong strike-slip extension developed the negative flower-shaped normal faults and the right-order swan-type faults and caused serious stratigraphic fragmentation. The amount of mud leakage increases with the increase of fault distance. Moreover, the closer to the fault, the higher the frequency and amount of mud leakage. When the distance between the wellbore and the fault exceeds 300 m, the possibility of mud leakage decreases significantly. The Silurian S1t is dominated by high-angle and vertical tension-shear fractures with good opening; while the S1k is dominated by low-angle structural and horizontal bedding fractures. The differences in fracture type cause the mud leakage in S1t to be significantly larger than that of S1k. In addition, the fracture development intervals identified by the R/S-FD method are in good agreement with the mud leakage intervals, which further indicates that the degree of fracture development is the key factor leading to the drilling mud leakage. The study also found that the degree of fracture development and the difference in horizontal principal stresses are the dominant factors leading to high Silurian mud leakage.